REKAYASA PROSES IRON SOFT MAGNETIC MELALUI MECHANICAL ALLOYING POWDER METALURGY BERBASIS SERBUK BESI LOKAL - Murjito . (Jurnal Gamma, 2012)
REKAYASA PROSES IRON SOFT MAGNETIC MELALUI MECHANICAL ALLOYING POWDER METALURGY BERBASIS SERBUK BESI LOKALMurjitoStaf Pengajar Jurusan Teknik Mesin, Fakultas Teknik Universitas Muhammadiyah Malang Email: moerjit@gmail.com, murjito@umm.ac.idABSTRACTSoft magnetic materials is a phenomenon that is interesting and unique, this uniqueness needs to be studied more deeply. Soft magnetic material (magnetic ferro) has been known since hundreds of years ago, but until now this process is still the process of making traditional process that is commonly used casting process. Casting process is still much to experience weaknesses and limitations, namely, melting energy is so high that no efficient, long process, the results can not be maximal, low dimensional accuracy, there is still further processes, and limited to certain elements, so that when it wants to make magnetic alloy of various elements or particles are still difficulties.To seek alternative production process of soft magnetic materials it is necessary to a solution or process engineering, on this occasion the researchers manipulate the process of soft magnetic material is iron with powder metalurgy mechanical alloying, in order to obtain the good soft magnetic iron and has high accuracy.In this study, researchers make the engineering process of soft magnetic iron production by mechanical alloying process based yan powder metalurgy local iron sands. Basis that the use of local sand backdrop of the results of the data that we can from raw materials and foundry industries penunjangsebagian materials are still imported. The ingredients are 100% pengadaanya still relies imported iron ore and materials are alloys (Alloy).The purpose of the study is the reverse process of soft magnetic iron by mechanical alloying of powder metalurgy process so that we will know the characteristics thermadinamika properties and mechanical properties of materials at various particle sizes up to the size of the micro / nano powder.Key word : soft magnetic materials, process engineering, mechanical alloying powder metalurgy